2011
DOI: 10.1111/j.2041-210x.2011.00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Combining static and dynamic variables in species distribution models under climate change

Abstract: Summary1. Methods used to predict shifts in species' ranges because of climate change commonly involve species distribution (niche) modelling using climatic variables, future values of which are predicted for the next several decades by general circulation models. However, species' distributions also depend on factors other than climate, such as land cover, land use and soil type. Changes in some of these factors, such as soil type, occur over geologic time and are thus imperceptible over the timescale of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
147
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(151 citation statements)
references
References 41 publications
3
147
0
1
Order By: Relevance
“…As land-use modification has left a strong historical legacy on the distribution of Iberian lynx and rabbits 8 , this information was used to constrain the suitability of ENM predictions, both for the present-day and future 29 . Our projections assume that lynx and rabbits will conserve their climatic-habitat preferences in the future and that land-use remains spatially constant.…”
Section: Methodsmentioning
confidence: 99%
“…As land-use modification has left a strong historical legacy on the distribution of Iberian lynx and rabbits 8 , this information was used to constrain the suitability of ENM predictions, both for the present-day and future 29 . Our projections assume that lynx and rabbits will conserve their climatic-habitat preferences in the future and that land-use remains spatially constant.…”
Section: Methodsmentioning
confidence: 99%
“…All spatial layers of these environmental variables were resampled to a resolution of 30 s to correspond to that of bioclimatic variables. Because reliable future projections of these variables (land cover, distance from residential areas, and roads) are not available, and because including static variables in SDMs alongside dynamic variables can improve model performance (Stanton et al, 2012), we kept these variables static in our projections.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Including static variables in SDMs when assessing climate-change effects on species distributions may improve model outputs (Stanton et al 2012). Stanton et al (2012) suggested excluding static variables highly correlated with climate variables, but that have indirect effects on the species distribution, such as altitude.…”
Section: Environmental Datamentioning
confidence: 99%